2019
DOI: 10.21037/atm.2019.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma: anatomical location-dependent clinical, prognostic, and genetic disparities

Abstract: Background: Anatomical location is considered in diagnostic and therapeutic approaches of cholangiocarcinoma (CCA). However, disparities and its extents in proportion of surgical candidates, prognostic factors, prognostic genetic networks, susceptibility for lymph node dissection, and disease stage at diagnosis remain to be confirmed. Methods: A total of 11,710 patients with cholangiocarcinoma from Surveillance, Epidemiology, and End Results Cancer Registries (SEER) and 45 CCA patients with paired tumor and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…These rates were different when classified only anatomically, when the highest survival rate in patients with DCCA was 65% at 1 year, 37.5% at 3 years, and 34.8% at 5 years, respectively. Our finding is contrast with what was found in a study by Hang and colleagues in 2019 which showing that the highest 5-year overall survival was found in ICCA (16.7%) followed by PCCA (16.4%) and DCCA (5.7%) [ 16 ]. The large difference of the 5-year survival rate among DCCA patients between this and our study, 5.7% versus 34.8%, could caused by various factors such as cause of the disease, cancer staging at time of surgery, surgical resectability, susceptibility to lymph node dissection, etc.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These rates were different when classified only anatomically, when the highest survival rate in patients with DCCA was 65% at 1 year, 37.5% at 3 years, and 34.8% at 5 years, respectively. Our finding is contrast with what was found in a study by Hang and colleagues in 2019 which showing that the highest 5-year overall survival was found in ICCA (16.7%) followed by PCCA (16.4%) and DCCA (5.7%) [ 16 ]. The large difference of the 5-year survival rate among DCCA patients between this and our study, 5.7% versus 34.8%, could caused by various factors such as cause of the disease, cancer staging at time of surgery, surgical resectability, susceptibility to lymph node dissection, etc.…”
Section: Discussioncontrasting
confidence: 99%
“…The survival of resected and unresected DCCA patients in the Netherlands between 2009 and 2016, had a median overall survival of 10.4 months across all stages; 21.9 months for resected, 6.7 months for unresected nonmetastatic, and 3.6 months for metastatic DCCA with the P was < 0.001 [15]. In 2019, there was a study performed in 11, 710 CCA patients from Surveillance, Epidemiology, and End Results Cancer Registries (SEER) compared survival for ICCA, PCCA, and DCCA and found that 5-year overall survival was highest in ICCA (16.7%) followed by PCCA (16.4%) and DCCA (5.7%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 , 36 ] For instance, the chance of having surgery for patients with ECCA was 36–37%, while that for patients with ICCA was 18.5%, which was associated with the rate of distant metastasis (ECCA vs ICCA, 30% vs 43.5%). [ 37 ] In addition, we found that older patients (>=50 years) had worse survival than younger patients (<50 years) in both ECCA and ICCA, which may be somewhat associated with better tolerance of the operation itself and fewer complications in younger patients. [ 7 , 9 , 38 ] With regard to CCA in the T1 stage, we found that patients with ICCA had better survival than those with ECCA before or after performing PSM.…”
Section: Discussionmentioning
confidence: 89%
“…Combined hepatocellular and cholangiocarcinoma (CHC) account for 0.4-14.2% of primary hepatic malignancies (1,2), originate from hepatic progenitor cells (3) and show both hepatocytic and cholangiocytic differentiation (4,5). In contrast, intrahepatic cholangiocarcinoma (ICC) is the second most common hepatic malignancy after hepatocellular carcinoma (6) and histologically derived from the biliary epithelial cell.…”
Section: Introductionmentioning
confidence: 99%